Between collateral damage and "iron law" - Emmanouilidis, Janis A. (Ελληνική Επιθεώρηση Πολιτικής Επιστήμης, 2017)
The article argues that the euro crisis has put European integration to a major test –more profound and more serious than ever before. Beyond the more immediate financial and economic effects, the crisis has inßicted collateral damage: unintended and unexpected consequences at both the national and European level, which could jeopardise not only the EU’s ability to manage (and overcome) the current crisis but also its ability toaddress future internal and external challenges. The article examines four of these consequences: (1) the growing distrust between national capitals and national societies; (2) the widening "democratic gap" at both EU and national level; (3) the new balance of power and the "new German question"; and, finally, (4) the acceleration of Europe’s global political and economic marginalisation.